Middle Ear Risk Index and results of pediatric tympanoplasty - adequate predictor? - André Carção; Pedro Marques Gomes; Diogo Cunha-Cabral; Delfim Duarte; Marta Neves (Revista Portuguesa Otorrinolaringologia e Cirurgia de Cabeça e Pescoço)
Aim: To assess the usefulness of the Middle Ear Risk Index (MERI) in adequately predicting the success of tympanoplasty in the pediatric population.